Algatika: Mathematics Private Lending Applications As An Effort To Increase Students Learning Interest In Mathematics Learning - Sari, Septi Rahmita; Sidik, Amelia T. R.; Yahya, Nisky Imansyah (Universitas Sebelas Maret, 2021)
In the era of sustainable development, education is a fundamental right for everyone. Education is a process of helping humans develop themselves so that they can face all problems with an open attitude. One way to help students clarify the concepts and understanding of mathematics that is being studied during the learning process is by using teaching aids. Teaching aids serve to facilitate the purpose of implementing learning in schools. However, the fact is that the use of mathematics teaching aids during learning at school is not yet entrenched, especially in areas far from urban areas, many of which do not have teaching aids. This directly impacts students' lack of understanding and learning experience, resulting in low student learning outcomes. This paper will introduce ALGATIKA, an application of lending mathematics teaching aids for elementary and junior high schools which can later solve these problems. The research methodology used is a qualitative descriptive method by deepening the material through literature studies. The result is that the lack of teaching aids in some schools can be overcome by the ALGATIKA application of lending mathematics teaching aids in elementary and junior high schools. Thus this application can help provide the teaching aids needed to build and improve educational facilities and provide an effective learning environment for all. It can develop students' teaching and learning processes and create higher quality education which leads to relevant and effective learning outcomes in accordance with the targets of the SDG's in education.